The Image of Stockholm in Pre-Modern Oral Tradition in Finland, Karelia and Ingria - Lamberg, Marko (Suomen Kansantietouden Tutkijain Seura, 2021)
This article analyses folkloric descriptions of Stockholm among the population of Finland and its neighbouring regions to the east and southeast which nowadays belong to the Russian Federation. As a transregional centre, Stockholm has affected the collective memory of people living relatively far away from the Swedish capital. This is the first study in which oral traditions are analysed in order to reconstruct the image of Stockholm among early modern Finnish, Karelian and Ingrian populations. Finnish, Karelian, and Ingrian are related languages. The collected traditions that were presented in these languages consist mostly of poems, or, more accurately, songs, which were composed by utilising the Kalevala metre. Some children’s rhymes are available in more westerly areas. The poems and rhymes do not actually depict Stockholm or its inhabitants. Instead, Stockholm is presented as a distant place and as a part of the real world. The poems often connect Stockholm to products, like nuts, knives, textiles and alcoholic beverages. Often it is a question of products that were shipped from Stockholm to other areas of the Baltic Sea Region. The poetic language uses Stockholm as a synonym or attribute to something valuable or rare. There are also poems that acknowledge the position of Stockholm as an administrative centre. The tradition maintained by the Swedish-speaking population in Finland is more diverse and Stockholm is mentioned more often in tales presented in prose. These tales also often mention merchandise. In addition, the export of Finnish goods to Stockholm is frequently mentioned. Stockholm is also depicted as a city and a place that can be visited. Occasionally, the tales also provide information on the city and its inhabitants. Even nonsensical children’s rhymes give more exact information than their counterparts in Finnish. Thanks to the common language and the greater geographic proximity, it was easier for Swedish speakers to interact with Stockholmers. The tradition presented in Finnish, Karelian, and Ingrian originates from areas which were situated further away. However, it is the traditions of Swedish-speakers that contain more elements of othering: according to several tales, it is, for example, possible to meet odd creatures on the sea when sailing to or from Stockholm. Even the city itself was sometimes presented as a part of a supernatural sphere, as witches and Sàmi with magical abilities were said to live there. Apparently, Stockholm was so well-known among the population of the Finnish archipelagos and in the coastal areas that its image could be coloured. Most likely, such tales were not always meant to be taken seriously. Artikkelissa tarkastellaan Suomen ja sen itäisten ja kaakkoisten lähialueiden suullisen kansanperinteen kuvauksia esimodernin ajan Tukholmasta. Ylialueellisena keskuspaikkana Tukholma on jättänyt jälkiä kaukanakin asuvien väestöjen kollektiiviseen muistiin. Folkloristisia aineistoja ei ole aiemmin hyödynnetty tarkasteltaessa näitä muistijälkiä ja niistä piirtyvää kuvaa. Suomen-, karjalan- ja inkerinkielinen perinne sisältää Tukholmaan liittyviä elementtejä lähinnä kalevalamittaisissa runoissa ja joissain läntisestä Suomesta kerätyissä lastenloruissa. Tukholmaa tai sen asukkaita ei varsinaisesti kuvata, vaan se näyttäytyy kaukaisena paikkana, osana tämänpuoleista maailmaa. Runokielessä Tukholma esiintyy kaukaisen tai epätavallisen synonyyminä tai määreenä: se liitetään usein tavaroihin, kuten pähkinöihin, veitsiin, kankaisiin ja alkoholijuomiin. Usein kyse on tuotteista, joita todella myös laivattiin Tukholman kautta muille pohjoisen Itämeren seuduille. Joistain runoista välittyy myös Tukholman asema hallinnollisena keskuksena. Suomen ruotsinkielinen perinne on monimuotoisempaa, ja Tukholma mainitaan useimmin proosamuotoisissa kertomuksissa. Niissäkin kuvataan usein kauppatavaroita, ja molemminpuolinen tavaranvaihto on selkeämmin läsnä. Tukholmaa kuvataan usein myös kaupunkina ja ympäristönä, jossa voidaan käydä ja liikkua. Myös kaupungin asukkaista ja topografiasta annetaan tietoja. Lastenloruperinnekin antaa suomenkielisiä loruja tarkempia tietoja Tukholmasta. Yhteisen kielen ja suuremman maantieteellisen läheisyyden ansiosta Suomen ruotsinkielisen väestön on ollut helpompi olla vuorovaikutuksessa Tukholman kanssa. Suomen-, karjalan- ja inkerinkielinen perinne on lisäksi peräisin lähes pääsääntöisesti kauempaa idästä. Kuitenkin nimenomaan ruotsinkielinen perinne toiseuttaa Tukholmaa esittäessään, että sinne suuntautuvan merimatkan aikana voidaan kohdata yliluonnollisia olentoja kuten naispuolisia vedenhaltijoita. Myös Tukholmaan itseensä voidaan liittää yliluonnolliseen sfääriin kuuluvia olentoja, kuten noitia ja noitataitoisia saamelaisia. Tukholma oli ruotsia puhuvalle väestölle sen verran tuttu, että sen kuvauksia voitiin värittää, epäilemättä joskus enemmän leikillään kuin tosissaan.